Investigation of the interaction of cyclic loading by force of chewing pressure and higher with the surface of composite endocrons and fixing cement - Makeev, V.; Skalskyy, V.; Pavlychko, R. (Actual Dentistry, 2018)
Introduction. To study the choice of materials and forms for endocrowns by studying their stability and wear under cyclic loading. Materials and Methods. Conducting mechanical tests for cyclic loading force of chewing pressure of 450 and 750 N dental materials – composite (Tetric N-Ceram and composite adhesive cement (RelyX™ U200) to install VUSM-500 with using the method of acoustic emission (AE) and SKOP-8M systems. ZEISS EVO 40XVP fragmentation research in the scanning electron microscope (CEM) and statistical processing of the data. Results. In the composite fatigue fracture occurred with rounded mikrokrater formed with arcuate ridges and mikrotrischy, we arranged from the center to the edges, actively developing after 53–60 thousand loading cycles. In the adhesive cement mikrokrater hemisphere is in the form of microcracks, located at the bottom, and the path macrocrack after 10–20 thousand. loading cycles. Conclusions. Under the influence of cyclic loading (500 thousand cycles), all dental materials were fatigued. The composite was the best indicator due to its high filling (81.5 %). Composite luting cement due to porosity caused by filling the lower indicator showed relatively low rates of wear because endocrown border and tabs for endodontic treated teeth are not recommended to place it at occlusions surface, especially at the occlusal contact point. Key words: endocrowns, composite, composite adhesive luting cement, cyclic loading, acoustic emission.